2012
DOI: 10.1145/2395123.2395127
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal behavior and interaction as indicators of cognitive load

Abstract: High cognitive load arises from complex time and safety-critical tasks, for example, mapping out flight paths, monitoring traffic, or even managing nuclear reactors, causing stress, errors, and lowered performance. Over the last five years, our research has focused on using the multimodal interaction paradigm to detect fluctuations in cognitive load in user behavior during system interaction. Cognitive load variations have been found to impact interactive behavior: by monitoring variations in specific modal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 68 publications
2
73
0
2
Order By: Relevance
“…This is especially true due to the time-sensitive or pressure-inducing nature of motor exercise tasks, as the user is attempting to maintain a certain pace, complete a number of repetitions within a time limit, or reach a certain progress goal [96].  Since information is being presented in parallel on three different aspects of a user's motion, selective attention toward one modality or domain may distract from learning in other domains.…”
Section: Disadvantagesmentioning
confidence: 99%
“…This is especially true due to the time-sensitive or pressure-inducing nature of motor exercise tasks, as the user is attempting to maintain a certain pace, complete a number of repetitions within a time limit, or reach a certain progress goal [96].  Since information is being presented in parallel on three different aspects of a user's motion, selective attention toward one modality or domain may distract from learning in other domains.…”
Section: Disadvantagesmentioning
confidence: 99%
“…Although the empirical findings have demonstrated promise for using handwriting features to detect mental workload, there is only a limited understanding of how to use changes in handwriting behavior to indicate mental workload. For example, there is still no general agreement on what detailed handwriting features are predictive of mental workload [6]- [8], [14]. The studies by Yu et al [8] and Lin et al [9] reported that pressure-related features were good indicators of mental workload, while Luria and Rosenblum [7] did not find significant differences in pressure-related features under three mental workload conditions.…”
Section: Related Workmentioning
confidence: 99%
“…handwriting process and speech) can often be collected implicitly without extra equipment, thereby increasing their applicability in real-world environments. Recently, the feasibility of employing changes in handwriting and verbal behavior to indicate mental workload has been identified by a few empirical findings [6], [7]. In the study, we are interested in handwriting behavior because it is pervasive in current educational environments.…”
Section: Introductionmentioning
confidence: 99%
“…Mental workload imposed on a person is an important component for human behavior modeling as it gives a direct representation of mental state of the person [1]. Cognitive load (CL) is the total amount of mental activity imposed on our working memory while doing any cognitive process.…”
Section: Introductionmentioning
confidence: 99%